Repressão política na terra das araucárias : a operação Marumbi em 1975 no Paraná - Brunelo, Leandro (2006)
This research analyzed the period of the military regime, specially the year of 1975, when happened in the State of Paraná a military police operation known as Operação Marumbi and that was planned and fired by DOPS and by CODI-DOI.The political police arrested more than 100 people accused of practicing communist activities in the State, specially the organization of the political bases of PCB. From this total of arrested people, 65 individuals were indicteds, initiating the IPM 745. This military police inquiry was collimated by the project Brasil: Nunca Mais when it reached the sphere of the Military Justice, nominated of BNM 551, and, through the documents that integrated it, mainly, the report elaborated by the police officer of DOPS who directed it to the Military Audit, the policial and judicial depositions that correspond to different phases of the process crime and the sentence uttered by the Public Military Ministry, was possible to identify the construction of a discourse that not only did emphasize that the militants of PCB were active executioners of a political crime, but also intended to involve the MDB as a political party infiltrated by the agents of the communism, due to the support supplied by the militants of PCB to the emedebistas candidates in 1974, when the elections for the representatives of the Legislative Power happened. Observing the IPM 745 or BNM 551 and the newspaper Folha de Londrina journal of 1983 that approached in your reports Operação Marumbi's backstage, it was possible to notice that besides arresting the politicians of PCB, there was the intention of diminishing the image of MDB to public opinion, accusing it of collusion with the communists due to the good performance obtained by the official opposition in the lawsuit of 1974. With that, it was intended to disarticulate the renascent popular opposition that gained force again to fight by the re-establishment for a democratic government in Brazil.